USING VISUAL AIDS TO IMPROVE ENGLISH COMPREHENSION IN TECHNICAL SUBJECTS (International Conference on Medical Science, Medicine and Public Health, 2025)
This paper discusses the use of visual aids in improving English language comprehension among engineering students. It emphasizes how visual materials such as diagrams, videos, and models can simplify technical concepts and support vocabulary acquisition. The article outlines different types of visual aids, their implementation in classroom settings, and their impact on student understanding and motivation. Challenges like resource limitations and overuse are also considered. The paper concludes that visual aids play a vital role in making technical English instruction more effective.